Parenting Style, Diet Pattern and Obesity of School-Age Children at Muhammadiyah University Elementary School, Purwokerto - Rizqa Ika Fitriyani; Izka Sofiyya Wahyurin; Pramesthi Widya Hapsari (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2023)
Background : Parenting style can influence the occurrence of obesity in children through their attitudes, habits, choices, and diet patterns. School-age children require a balanced nutritional intake to support their growth and development. Therefore, parents need to pay great attention to their child's nutrition to ensure that their growth and development processes are not disrupted and to prevent various illnesses. The purpose of this study was to determine the relationship between parenting style and diet patterns with the incidence of obesity in school-age children at Muhammadiyah University Elementary School, Purwokerto Methods : This research used a cross-sectional design with purposive sampling. The total number of respondents in this study was 46 students. The Parenting Styles and Dimensions Questionnaire (PSDQ) was used to assess parenting styles, while the Food Frequency Questionnaire was used to determine the diet patterns of the respondents.The data analysis used in this study was the Spearman correlation test. Results : The results of the bivariate analysis indicate that there is no significant relationship between parenting style and obesity (p=0.331). However, there is a significant association between fast food consumption and obesity (p=0.000), while there is no significant association between the consumption of sugar-sweetened beverages and obesity (p=0.309). Conclusions : There was no association found between parenting style and the consumption of sugar-sweetened beverages with obesity. However, a significant association was observed between fast food consumption and obesity among school-age children at Muhammadiyah University Purwokerto Primary School.